Healing Interpersonal and Racial Trauma: Integrating Racial Socialization Into Trauma-Focused Cognitive Behavioral Therapy for African American Youth. (February 2021) - Metzger, Isha W.; Anderson, Riana Elyse; Are, Funlola; Ritchwood, Tiarney
African American youth are more likely than their peers from other racial and ethnic groups to experience interpersonal traumas and traumatic racist and discriminatory encounters. Unfortunately, evidence-based trauma treatments have been less effective among these youth likely due to these treatments not being culturally tailored to address both interpersonal and racial trauma. In this article, we utilize the racial encounter coping appraisal and socialization theory to propose suggestions for adapting trauma-focused cognitive behavioral therapy—an evidence-based trauma treatment for children and adolescents—to include racial socialization or the process of transmitting culture, attitudes, and values to help youth overcome stressors associated with ethnic minority status. We conclude by discussing implications for the research and clinical community to best promote healing from both interpersonal and racial trauma for African American youth.